Case Report: Sequential Transarterial and Trans-Cortical Venous Embolization of a Mixed Pial-Dural AVM - Yeboah, Kevin; Fares, Mary-Ann; Hansen, Paul; Yoo, Albert J. (Frontiers in Neurology, 2022)
Endovascular therapy is the primary treatment modality for dural arteriovenous fistulas. Pre-treatment angiographic evaluation of dural fistulas must rule out the presence of a mixed pial component or supply from pial-dural collaterals, as the pial supply must be closed before definitive occlusion of the draining vein to prevent iatrogenic rupture. Here we describe a case of a mixed pial-dural AVM, which was effectively treated with a sequential transarterial and trans-cortical venous embolization.